Simulation and dSPACE Based Implementation of Various PWM Strategies for A New H-Type FCMLI Topology - Chinnapettai Ramalingam Balamurugan; S.P. Natarajan; T.S. Anandhi; B. Shanthi (Institute of Advanced Engineering and Science, 2015)
Depending on the number of levels in output voltage, inverters can be divided into two categories: two level inverter and Multi Level Inverters (MLIs). An inverter topology for high voltage and high power applications that seems to be gaining interest is the MLI. In high power and high voltage applications, the two level inverters have some limitations in operating at high frequency mainly due to switching losses and constraints of device rating.In this paper, a three phase H + type FCMLI (Flying Capacitor MLI) using sinusoidal reference, third harmonic injection reference, 60 degree reference and stepped wave reference are initially developed using SIMULINK and then implemented in real time environment using dSPACE. In H-type FCMLI with R-load it is inferred that bipolar COPWM-C provides output with relatively low distortion for 60 degree reference and bipolar COPWM-C strategy is found to perform better since it provides relatively higher fundamental RMS output voltage for THI reference. The five level output voltages of the chosen MLIs obtained using the MATLAB and dSPACE based PWM (Pulse Width Modulation) strategies and the corresponding %THD (Total Harmonic Distortion), VRMS (fundamental), CF (Crest Factor) and FF (Form Factor) are presented and analyzed.